Electroencephalography during functional echo-planar imaging: Detection of epileptic spikes using post-processing methods - Hoffmann, A.; Jäger, L.; Werhahn, K.J.; Jaschke, M.; Noachtar, S.; Reiser, M. (Magnetic resonance in medicine, 2000)
EEG has been used to trigger functional MRI of patients with focal epilepsy, but EEG can be obscured by artifacts during MR data acquisition, and no continuous correlation of EEG and MRI has been possible without limiting the image time. Artifacts caused by an MRI sequence were investigated in five healthy subjects, and an EEG of five patients with epileptic discharges was recorded during echo‐planar imaging. All interfering frequencies in the EEG were discrete and defined by loop structures in the MRI sequence. In post‐processing of the EEG interfering frequencies were automatically detected by comparing the frequency spectra of the EEG recorded before and during imaging. After elimination of interfering frequencies by filters in the time domain or by Fourier transform, reliable spike detection in the EEG recorded during MR data acquisition became feasible, without loss of EEG quality. Magn Reson Med 44:791–798, 2000. © 2000 Wiley‐Liss, Inc.